2002
DOI: 10.1080/090647102321089837
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Rates and Method of Nitrogen Application on Dry Matter Yield and some Characters of Sorghum-Sudangrass Hybrid

Abstract: Iptas, S. and Brohi, A. R. (Faculty of Agriculture, Gaziosmanpas a University, TR-60240 Tokat, Turkey). Effect of nitrogen rates and method of nitrogen application on dry matter yield and some characters of sorghum -sudangrass hybrid.In this study, the effect of nitrogen (N) rates (0, 40, 80, 120, 160 and 200 kg N ha ¼ 1 ) and methods of N application (A 1 : all N at sowing; A 2 : no N at sowing, half N after the rst cutting and the remaining half after the second cutting; A 3 : one-third N at sowing, one-thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
3
1
0
1
Order By: Relevance
“…The higher number of tillers associated with Buffel grass could be ascribed to its deep rooting system and a high potential for regrowth due to the space provided during planting and easy uptake of nitrogen fertilizer during the second season. The results agree with Iptas and Brohi's [48] findings, which recorded an escalation in the number of tillers with nitrogen application in Sudan grass. From the aforementioned growth parameters, it is clear that nitrogen fertilizer application positively and significantly affects the growth of both kinds of grass [5].…”
Section: Discussionsupporting
confidence: 91%
“…The higher number of tillers associated with Buffel grass could be ascribed to its deep rooting system and a high potential for regrowth due to the space provided during planting and easy uptake of nitrogen fertilizer during the second season. The results agree with Iptas and Brohi's [48] findings, which recorded an escalation in the number of tillers with nitrogen application in Sudan grass. From the aforementioned growth parameters, it is clear that nitrogen fertilizer application positively and significantly affects the growth of both kinds of grass [5].…”
Section: Discussionsupporting
confidence: 91%
“…The results also showed in Table ( 4) that the level of fertilization was 50 kg N ha -1 , as it gave the highest mean for the trait, which amounted to 1562.15 leaves M -2 , without a significant difference from the level of 75 kg N ha -1 , which had an average of 1536.37 leaves M -2 , while a treatment was given The comparison (without adding) the lowest mean for the trait reached 1203.52 seedlings m -2 , and the reason for this may be due to the fact that increasing the amount of nitrogen fertilizer added in a way that meets the plant's need (50 kg N ha -1 ) helped to increase root growth and stimulate lateral shoots and thus encourage The emergence, growth and development of shoots and an increase in tillering per unit area as a natural result of an increase in the number of tillers in the plant. This result agreed with the findings of [7], where they indicated that increasing levels of nitrogen fertilizer led to an increase in the number of branches per plant.…”
Section: Total Number Of Tillers (M 2 )supporting
confidence: 92%
“…From the results of Table (8), we note that there are significant differences between the planting distances in their effect on the percentage of protein in the plant, as the distance 70 cm gave the highest mean for the trait amounted to 9.96%, while the distance 40 cm gave the lowest mean for the trait amounted to 9.54%, which did not differ significantly from the distance 50 cm, giving an average of 9.62%. The reason for this may be that the distance of 70 cm between the lines has provided a better opportunity for plants in terms of growth, especially root growth due to the lack of competition, which made the absorption of nitrogen better and in a higher quantity as a result of the small number of plants per unit area, and that an increase in absorption necessarily means an increase in the concentration of nitrogen In plant tissues, which led to an increase in its percentage in the vegetative part, and the result agreed with [7], who noticed that increasing the plant distance increases the percentage of protein in the leaves. Results in the same table showed that the fertilization level of 75 kg N ha -1 was superior, as it gave the highest mean for the trait amounted to 10.99%, while the comparison treatment gave the lowest average for the trait amounted to 7.54%.…”
Section: The Plant Protein (%)supporting
confidence: 53%
See 1 more Smart Citation
“…작물의 생산 효율성은 토양 비옥도에 따라 결정되며, 토양 비옥도는 다량 영양소와 미량 영양소의 가용성에 따라 결정된다 (Tale and Ingole, 2015). 질소는 아미노산, 엽록소, 핵산, ATP 및 식물 호르몬과 1차 또는 2차 대사산물의 구성 원소로써 (Frink et al, 1999) (Choi et al, 2022), 공급량과 방법은 기후, 토양 비옥도, 품종 및 이용목적에 따라 달라진다 (Iptas and Brohi, 2002). 따라서 양분 손실을 최소화하면서 작물의 수량과 품질을 향상시키기 위해서는 수단그라스 재배지의 토 양 및 식물 영양 특성을 파악하고 두 특성 간에 미치는 영향에 대한 분석을 통해 생산성을 평가하고 적정 비료량을 설 정하는 것이 중요하다.…”
Section: Introductionunclassified